2003
DOI: 10.4049/jimmunol.170.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Platelet-Activating Factor Acetylhydrolase in Macrophages and Monocyte-Derived Dendritic Cells

Abstract: Although macrophages (Mφ) and monocyte-derived dendritic cells (MDDC) come from a common precursor, they are distinct cell types. This report compares the two cell types with respect to the metabolism of platelet-activating factor (PAF), a biologically active lipid mediator. These experiments were prompted by our studies of localized juvenile periodontitis, a disease associated with high IgG2 production and a propensity of monocytes to differentiate into MDDC. As the IgG2 Ab response is dependent on PAF, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
3
27
0
1
Order By: Relevance
“…We found that IFN-␥ , which has been implicated as a promoter of foam cell formation and an inducer of M1 pro-infl ammatory phenotypes ( 47 ), decreased expression of Lp-PLA 2 at the transcriptional level ( 48 ). Conversely, M-CSF, which induces an M2-like, anti-infl ammatory phenotype, increased monocyte Lp-PLA 2 expression to a much higher extent compared with the M1-inducer GM-CSF ( 49 ). However, Ferguson and coworkers reported modest increases or no changes in Lp-PLA 2 mRNA levels in M1 and M2 macrophages, respectively, using different induction strategies ( 44 ).…”
Section: Cellular Sources and Regulation Of Expressionmentioning
confidence: 75%
“…We found that IFN-␥ , which has been implicated as a promoter of foam cell formation and an inducer of M1 pro-infl ammatory phenotypes ( 47 ), decreased expression of Lp-PLA 2 at the transcriptional level ( 48 ). Conversely, M-CSF, which induces an M2-like, anti-infl ammatory phenotype, increased monocyte Lp-PLA 2 expression to a much higher extent compared with the M1-inducer GM-CSF ( 49 ). However, Ferguson and coworkers reported modest increases or no changes in Lp-PLA 2 mRNA levels in M1 and M2 macrophages, respectively, using different induction strategies ( 44 ).…”
Section: Cellular Sources and Regulation Of Expressionmentioning
confidence: 75%
“…Recent observations indicate that the monocytes of subjects with localized aggressive periodontitis (LAgP) have a propensity to differentiate into dendritic cells, which synthesize and secrete much less PAF-AH than macrophages (53). This raises the possibility that, compared with controls, LDLs from subjects with periodontitis may contain less PAF-AH activity and, as a result, lack the protective, antiatherogenic influence that this enzyme may have.…”
mentioning
confidence: 80%
“…Although PAF-AH expression increases when monocytes differentiate into macrophages or dendritic cells (53,70), dendritic cells express much lower levels of the enzyme than macrophages. We have shown previously that, in culture, monocyte-derived dendritic cells of subjects with LAgP (then called localized juvenile periodontitis) synthesize and secrete much less PAF-AH activity than monocytederived macrophages (53).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the kinetics and magnitude of PAF AH expression are different in primary macrophage populations that differ in CD14 and CD16 expression levels. 3 Moreover, differentiation of monocytes into dendritic cells results in significantly lower levels of intracellular and secreted PAF AH activity compared with macrophages (49). A key contribution of the present study is the utilization of a murine model system that mimics in vivo responses in cells that are not terminally differentiated and, thus, potentially recapitulates events that occur when monocytic cells are recruited and induced to differentiate in inflamed tissues in vivo.…”
Section: Lps Stimulation Enhances the Transactivation Function Of Sp1mentioning
confidence: 95%